A taste of power : food and American identities - Vester, Katharina (California studies in food and culture, 2015)
"A Taste of Power is an investigation of the crucial role culinary texts and practices played in the making of cultural identities and social hierarchies since the founding of the United States. Nutritional advice and representations of food and eating, including cookbooks, literature, magazines, newspapers, still life paintings, television shows, films, and the internet, have helped throughout American history to circulate normative claims about citizenship, gender performance, sexuality, class privilege, race, and ethnicity, while promising an increase in cultural capital and social mobility to those who comply with the prescribed norms. The study examines culinary writing and practices as forces for the production of social order and, at the same time, as points of cultural resistance against hegemonic norms, especially in shaping dominant ideas of nationalism, gender, and sexuality, suggesting that eating right is a gateway to becoming an American, a good citizen, an ideal man, or a perfect mother. Cookbooks, as a low-prestige literary form, became the largely unheralded vehicles for women to participate in nation-building before they had access to the vote or public office, for middle-class authors to assert their class privileges, for men to claim superiority over women even in the kitchen, and for Lesbian authors to reinscribe themselves into the heteronormative economy of culinary culture. The book engages in close reading of a wide variety of sources and genres to uncover the intersections of food, politics, and privilege in American culture"--Provided by publisher.